BRI dan Peran Mediasi Cina: Analisis Kepentingan Nasional dalam Konflik Palestina-Israel - Ahmad Rifqih Ghazali (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
The Belt and Road Initiative (BRI) is China's foreign policy introduced during the administration of Xi Jinping. This policy represents China's efforts to expand cooperation in the economic sector and aims to shift the United States' hegemony, both in security and particularly in the economic domain. The project spans across various regions, including the Middle East, a region abundant in energy resources and petroleum, prompting China to focus on collaboration with Arab nations. This approach has been positively received by countries in the Middle East as China adopts a proactive method without military intervention, concentrating solely on economic cooperation. Furthermore, China's recent appointment as the Chair of the United Nations Security Council presents an opportune moment. This positions China to play a more significant role in its extensive projects, serving as a mediator for peace in the Palestine-Israel conflict. This article seeks to address questions regarding China's interests as the Chair of the UN Security Council in the Palestine-Israel conflict, employing the theories of hegemonic stability and the concept of national interest.